2018
DOI: 10.48550/arxiv.1806.05814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exact dimer phase with anisotropic interaction for one dimensional magnets

Hong-Ze Xu,
Shun-Yao Zhang,
Guang-Can Guo
et al.

Abstract: We report the exact dimer phase, in which the ground states are described by product of singlet dimer, in the extended XYZ model by direct generalizing the isotropic Majumdar-Ghosh model to the fully anisotropic regime. This model also supports three different ferromagnetic (FM) phases, denoted as x-FM, y-FM and z-FM. The boundaries between the dimer phase and FM phases are infinite-fold degenerate. The breaking of this infinite-fold degeneracy by either translational symmetry or Z2 symmetry lead to dimer phas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…LiInCr 4 O 8 was found to be spin-3/2 breathing pyrochlore antiferromagnet, which is an alternating array of small and large tetrahedra [10]. Recently, it is reported that the results from the dimer anisotropic XYZ model are relevant to a large number of quasi-one dimensional magnets [11]. In history, Bulaevskii predicted that a spin gap exists in the nonuniform antiferromagnetic (AFM) spin chains [12].…”
Section: Introductionmentioning
confidence: 99%
“…LiInCr 4 O 8 was found to be spin-3/2 breathing pyrochlore antiferromagnet, which is an alternating array of small and large tetrahedra [10]. Recently, it is reported that the results from the dimer anisotropic XYZ model are relevant to a large number of quasi-one dimensional magnets [11]. In history, Bulaevskii predicted that a spin gap exists in the nonuniform antiferromagnetic (AFM) spin chains [12].…”
Section: Introductionmentioning
confidence: 99%